Improving Writing Proficiency through The 3M (Meniru-Mengolah-Mengembangkan) Writing Strategy for Grade VI SD Negeri 8 Kilensari Panarukan Sub-District of Situbondo District in 2014/2015 Academic Year - Sukasih Sukasih (Pancaran Pendidikan, 2018)
Students have a different level of prose writing proficiency. Some students are already able to write a prose pretty well while some others are not. This condition is aggravated by students’ low motivation in writing. Therefore, an effective writing learning strategy is needed. In teaching and learning process, especially in a school environment, teachers play an important role so that a learning strategy serves as a tool to improve learning. The research design used was CAR – collaborating another teacher – that was set to 2 cycles. Based on the research findings of the implementation of 3M prose writing strategy in the first cycle, students who passed were by 50% of 18 students. In the second cycle, on the other hand, students who passed were about 89%. It means that there was 39% improvement from the first cycle. We can see that the implementation of 3M prose writing strategy can improve the sixth-grade students’ prose writing proficiency at SD Negeri 8 Kilensari Panarukan Situbondo Academic Year of 2014/2015.